2021
DOI: 10.1007/s00405-021-07103-x
|View full text |Cite
|
Sign up to set email alerts
|

Music perception and speech intelligibility in noise performance by Italian-speaking cochlear implant users

Abstract: Objective The goal of this study was to investigate the performance correlations between music perception and speech intelligibility in noise by Italian-speaking cochlear implant (CI) users. Materials and methods Twenty postlingually deafened adults with unilateral CIs (mean age 65 years, range 46–92 years) were tested with a music quality questionnaire using three passages of music from Classical Music, Jazz, and Soul. Speech recognition in noise was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The strength of correlations shows a considerable variability (weak to strong), with a trend towards stronger relationships of melody/total Gordon scores with HI and WRSn + 10. Such significant relationships are in line with previous findings from adult CI users [ 12 , 13 , 22 ] and as promising as those from recent studies showing significant positive effects of music training on speech-in-noise understanding [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The strength of correlations shows a considerable variability (weak to strong), with a trend towards stronger relationships of melody/total Gordon scores with HI and WRSn + 10. Such significant relationships are in line with previous findings from adult CI users [ 12 , 13 , 22 ] and as promising as those from recent studies showing significant positive effects of music training on speech-in-noise understanding [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, auditory perception through CI appears satisfying in allowing speech processing in quiet [ 11 ] but is still very limited in providing access to fine details of spectro-temporal variations in speech-in-noise and music [ 10 ]. Consistently with previous studies [ 12 , 13 , 21 ], present CIC versus THC performance comparisons for LF pitch, speech-in-noise, and all music measures (rhythm, melody, and overall) except harmony reveal statistically significant differences with large effect sizes whereas both groups seem to obtain excellent scores for speech perception in quiet (scores equal or above 90% even in all CIC). CIC performances for harmony are also considerably poorer than those of THC, but statistically significant differences disappear for this measure after Bonferroni correction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Music perception has been shown to be highly variable in CI users (Drennan et al, 2015;Gfeller et al, 2008;Philips et al, 2012;Wright & Uchanski, 2012) and correlated with speech perception in noise where individuals with better speech perception in noise report higher levels of listening and enjoyment of music (Dincer D'Alessandro et al, 2021). Previous studies have found difficulties when investigating CI users listening to lyrical music; this may suggest that the instrument accompaniment of lyrical music might act as background noise while they attempt to hear and understand the lyrics (Collister & Huron, 2008;Eskridge et al, 2012;Gfeller et al, 2008Gfeller et al, , 2019.…”
Section: Ciqol: Entertainmentmentioning
confidence: 99%